Efforts to Empower the Community in the Effort to Keep the River Clean Through Collective Activities and Spreading Catfish and Tilac Seeds in Gunung Handeuleum Village - Fadli Pribadi, Muhamad; Fathimah, Anissatul (AMK : Abdi Masyarakat UIKA, 2022)
Community behavior in protecting and preserving the environment is minimal, including in keeping the river clean, the main thing that causes river pollution is garbage. Garbage problems are common in various regions in Indonesia, including in the Bogor Regency area, where waste is still a serious problem. Therefore, the aim is to empower the community through a river cleaning program and spread catfish and tilapia seeds which will later reproduce so that they can be used for the community, then carry out mutual cooperation activities in an effort to keep the river clean to improve polluted river ecosystems and it is hoped that local residents will become care more about the river environment. The method used in this study is a direct survey, to see the condition of the river and the level of pollution by garbage and the number of fish in the river. The results of community empowerment in maintaining the cleanliness of the river are carrying out mutual cooperation activities to clean up trash from the river, spread catfish and tilapia seeds and provide water hyacinth plants. Thus it can be concluded that community empowerment activities in keeping the river clean are effective in reducing river pollution so that the river becomes clean and beneficial for the local community.